2007
DOI: 10.1016/j.gene.2007.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Direct inhibition of CDK9 blocks HIV-1 replication without preventing T-cell activation in primary human peripheral blood lymphocytes

Abstract: HIV-1 transcription is essential for the virus replication cycle. HIV-1 Tat is a viral transactivator that strongly stimulates the processivity of RNA polymerase II (RNAPII) via recruitment of the cyclin T1/CDK9 positive transcription elongation factor, which phosphorylates the C-terminal domain (CTD) of RNAPII. Consistently, HIV-1 replication in transformed cells is very sensitive to direct CDK9 inhibition. Thus, CDK9 could be a potential target for anti-HIV-1 therapy. A clearer understanding of the requireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 40 publications
2
47
0
Order By: Relevance
“…7 Targeting of P-TEFb with the CDK inhibitor flavopiridol inhibits HIV expression, 8 but has unfavorable toxicities. [9][10][11] Indirubin, another CDK inhibitor, 12 is the active ingredient of the traditional Chinese herbal formula Dan Gui Long Hui Wan, used to treat chronic myelogenous leukemia and psoriasis. 13 We have previously demonstrated that indirubin-3¢-monoxime (IM), a derivative of indirubin with improved solubility, is an inhibitor of CDK9 and P-TEFb function that blocks HIV gene expression in the absence of toxicity.…”
mentioning
confidence: 99%
“…7 Targeting of P-TEFb with the CDK inhibitor flavopiridol inhibits HIV expression, 8 but has unfavorable toxicities. [9][10][11] Indirubin, another CDK inhibitor, 12 is the active ingredient of the traditional Chinese herbal formula Dan Gui Long Hui Wan, used to treat chronic myelogenous leukemia and psoriasis. 13 We have previously demonstrated that indirubin-3¢-monoxime (IM), a derivative of indirubin with improved solubility, is an inhibitor of CDK9 and P-TEFb function that blocks HIV gene expression in the absence of toxicity.…”
mentioning
confidence: 99%
“…As substantiated by recent evidence (4,5), many host requirements are conserved among related viruses, increasing the possibility for broad-spectrum antiviral activity. Likewise, the host-directed approach may contribute to reducing the frequency of viral escape from inhibition (6)(7)(8), since individual viral mutations are less likely to compensate for functional loss of a host factor or pathway required for viral replication.…”
mentioning
confidence: 99%
“…HIV-1 Tat assists in this process by competitively displacing HEXIM1 to free P-TEFb from the inhibitory complex (4,64). Activated P-TEFb is then recruited to nascent HIV-1 transcripts, where it facilitates transcript elongation and thus reactivation of latent virus (38,63,70,76).…”
mentioning
confidence: 99%